Domestic cat density is not associated with variation in avian risk assessment in a mega-city - Pranav Bellur; Mario Díaz; Travis Longcore; Daniel T. Blumstein (Urban Ecosystems, 2026)
Domestic cats ( Felis catus ) kill an estimated 1.3–4.0 billion birds annually in the United States and are a major source of mortality for urban birds. While their lethal impacts are well documented, fewer studies address sublethal effects such as changes in avian risk assessment. We analyzed a dataset of 1,120 experimental approaches by human observers on 48 bird species across 11 sites in the Los Angeles metropolitan area, which varied in free-roaming cat and human population densities. Using Bayesian mixed models, we examined ecological and intrinsic predictors of avian flight initiation distance (FID). At the community scale, cat and human population densities had no significant effects on FID, suggesting that predator and human presence may already exceed a threshold across the urban landscape beyond which additional variation does not produce detectable changes in avian escape behavior. Species-specific analyses revealed that black phoebe ( Sayornis nigricans ) FID increased with human population density. We found no community-level interaction effect of human density and cat density, but house finches ( Carpodacus mexicanus ) and rock pigeons ( Columba livia ) tolerated closer approaches in areas with both high human and cat density, suggesting that habituation to humans may lower perceived predation risk for some urban species. Heavier species, ground-foraging individuals, and actively foraging birds had shorter FIDs. Birds also flushed at greater distances as the time of day progressed. These results highlight the complex interplay of intrinsic and environmental factors shaping avian escape behavior and underscore how behavioral adaptation in megacities may alter predator–prey dynamics in urban landscapes.

Assessing and mapping taxon-specific effects of ecological light pollution for environmental impact analysis - Travis Longcore; Brittany Lynch; Kaitlyn Phelan; Debbie Melton; Dane Sanders; Michael Herf (Biological Conservation, 2026)

Smartphone location data show park use patterns in extreme heat (Los Angeles, California, USA) - Bethany Woo; Samara Fruman; Renato Escobar; Alondra Gallegos; Jasmine Kim; Jana Salomon; Danielle Sonobe; Jeffrey Van; Sahar Derakhshan; Travis Longcore (Landscape and Urban Planning, 2026)

Smartphone locations reveal patterns of cooling center use as a heat mitigation strategy - Sahar Derakhshan; Trisha N. Bautista; Mari Bouwman; Liana Huang; Lily Lee; Jo Tarczynski; Ian Wahagheghe; Xinyi Zeng; Travis Longcore (Applied Geography, 2023)

A science-based policy for managing free-roaming cats - Christopher A. Lepczyk; David C. Duffy; David M. Bird; Michael Calver; Dmitry Cherkassky; Linda Cherkassky; Christopher R. Dickman; David Hunter; David Jessup; Travis Longcore; Scott R. Loss; Kerrie Anne T. Loyd; et al. (Biological Invasions, 2022)

Commentary: Brightness of the Night Sky Affects Loggerhead (Caretta caretta) Sea Turtle Hatchling Misorientation but Not Nest Site Selection - Travis Longcore; Dan Duriscoe; Martin Aubé; Andreas Jechow; Christopher C. M. Kyba; Kellie L. Pendoley (Frontiers in Marine Science, 2020)

Correction to: Responding to misinformation and criticisms regarding United States cat predation estimates - Scott R. Loss; Tom Will; Travis Longcore; Peter P. Marra (Biological Invasions, 2018)

Responding to misinformation and criticisms regarding United States cat predation estimates - Scott R. Loss; Tom Will; Travis Longcore; Peter P. Marra (Biological Invasions, 2018)

Genomic data indicate ubiquitous evolutionary distinctiveness among populations of California metalmark butterflies - Julian R. Dupuis; Jeffrey C. Oliver; Bryan M. T. Brunet; Travis Longcore; Jana J. Johnson; Felix A. H. Sperling (Conservation Genetics, 2018)

Belowground interactions with aboveground consequences: Invasive earthworms and arbuscular mycorrhizal fungi - Shishir Paudel; Travis Longcore; Beau MacDonald; Melissa K. McCormick; Katalin Szlavecz; Gail W. T. Wilson; Scott R. Loss (Ecology, 2016)
A mounting body of research suggests that invasive nonnative earthworms substantially alter microbial communities, including arbuscular mycorrhizal fungi ( AMF ). These changes to AMF can cascade to affect plant communities and vertebrate populations. Despite these research advances, relatively little is known about (1) the mechanisms behind earthworms’ effects on AMF and (2) the factors that determine the outcomes of earthworm– AMF interactions (i.e., whether AMF abundance is increased or decreased and subsequent effects on plants). We predict that AMF ‐mediated effects of nonnative earthworms on ecosystems are nearly universal because (1) AMF are important components of most terrestrial ecosystems, (2) nonnative earthworms have become established in nearly every type of terrestrial ecosystem, and (3) nonnative earthworms, due to their burrowing and feeding behavior, greatly affect AMF with potentially profound concomitant effects on plant communities. We highlight the multiple direct and indirect effects of nonnative earthworms on plants and review what is currently known about the interaction between earthworms and AMF . We also illustrate how the effects of nonnative earthworms on plant– AMF mutualisms can alter the structure and stability of aboveground plant communities, as well as the vertebrate communities relying on these habitats. Integrative studies that assess the interactive effects of earthworms and AMF can provide new insights into the role that belowground ecosystem engineers play in altering aboveground ecological processes. Understanding these processes may improve our ability to predict the structure of plant and animal communities in earthworm‐invaded regions and to develop management strategies that limit the numerous undesired impacts of earthworms.

Remote sensing to map influence of light pollution on Cory’s shearwater in São Miguel Island, Azores Archipelago - Pedro Rodrigues; Christoph Aubrecht; Artur Gil; Travis Longcore; Chris Elvidge (European Journal of Wildlife Research, 2012)

Extracting useful data from imperfect monitoring schemes: endangered butterflies at San Bruno Mountain, San Mateo County, California (1982–2000) and implications for habitat management - Travis Longcore; Christine S. Lam; Patrick Kobernus; Eben Polk; John P. Wilson (Journal of Insect Conservation, 2010)

Historical Ecology as a Tool for Assessing Landscape Change and Informing Wetland Restoration Priorities - Eric D. Stein; Shawna Dark; Travis Longcore; Robin Grossinger; Nicholas Hall; Michael Beland (Wetlands, 2010)

Critical Assessment of Claims Regarding Management of Feral Cats by Trap–Neuter–Return - TRAVIS LONGCORE; CATHERINE RICH; LAUREN M. SULLIVAN (Conservation Biology, 2009)
Many jurisdictions have adopted programs to manage feral cats by trap–neuter–return (TNR), in which cats are trapped and sterilized, then returned to the environment to be fed and cared for by volunteer caretakers. Most conservation biologists probably do not realize the extent and growth of this practice and that the goal of some leading TNR advocates is that cats ultimately be recognized and treated as “protected wildlife.” We compared the arguments put forth in support of TNR by many feral cat advocates with the scientific literature. Advocates promoting TNR often claim that feral cats harm wildlife only on islands and not on continents; fill a natural or realized niche; do not contribute to the decline of native species; and are insignificant vectors or reservoirs of disease. Advocates also frequently make claims about the effectiveness of TNR, including claims that colonies of feral cats are eventually eliminated by TNR and that managed colonies resist invasion by other cats. The scientific literature contradicts each of these claims. TNR of feral cats is primarily viewed and regulated as an animal welfare issue, but it should be seen as an environmental issue, and decisions to implement it should receive formal environmental assessment. Conservation scientists have a role to play by conducting additional research on the effects of feral cats on wildlife and by communicating sound scientific information about this problem to policy makers.

Management by Assertion: Beavers and Songbirds at Lake Skinner (Riverside County, California) - Travis Longcore; Catherine Rich; Dietland Müller-Schwarze (Environmental Management, 2007)

Analysis of Transect Counts to Monitor Population Size in Endangered Insects The Case of the El Segundo Blue Butterfly, Euphilotes Bernardino Allyni - Rudi Mattoni; Travis Longcore; Cor Zonneveld; Vojtech Novotny (Journal of Insect Conservation, 2001)

ENVIRONMENTAL AUDITING: Arthropod Monitoring for Fine-Scale Habitat Analysis: A Case Study of the El Segundo Sand Dunes - Rudi Mattoni; Travis Longcore; Vojtech Novotny (Environmental Management, 2000)